(untitled) (Italian Review of Legal History, 2015)
Milano, 1827. The criminal proceeding against Count Giuseppe Brebbia, a Lombardo-Venetian’ senior official accused of misfeasance, is of considerable significance to investigate the interlinkage between social classes and administration assessment in the first years of Austrian restoration in Italy. At that time, undeniable signs of Adelstand’s difficulties in handling public affair occurred, mainly at local level. The questions of how and why an impersonal administration rose can be answered only taking a closer look at this trial, around which many social and political interests clustered around.